2017
DOI: 10.1038/srep41055
|View full text |Cite
|
Sign up to set email alerts
|

Decoding the role of the nuclear receptor SHP in regulating hepatic stellate cells and liver fibrogenesis

Abstract: The small heterodimer partner (SHP) is an orphan nuclear receptor that lacks the DNA binding domain while conserves a putative ligand-binding site, thought that endogenous ligands for this receptor are unknown. Previous studies have determined that SHP activation protects against development of liver fibrosis a process driven by trans-differentiation and activation of hepatic stellate cells (HSCs), a miofibroblast like cell type, involved in extracellular matrix (ECM) deposition. To dissect signals involved in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…The importance of this regulation is illustrated in mice lacking SHP, which show increased sensitivity to BDL secondary to increased basal expression of Cyp7a1 and increased bile flow (30, 31). The protective effect of SHP is also seen in several other studies where loss of SHP results in dysregulation of BA synthesis, while activation of SHP in hepatic stellate cells attenuates fibrosis (32, 33). Thus, the increased SHP expression seen in β-catenin KO after BDL is in line with previous reports describing an improvement in phenotype through reduction of BA synthesis and metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…The importance of this regulation is illustrated in mice lacking SHP, which show increased sensitivity to BDL secondary to increased basal expression of Cyp7a1 and increased bile flow (30, 31). The protective effect of SHP is also seen in several other studies where loss of SHP results in dysregulation of BA synthesis, while activation of SHP in hepatic stellate cells attenuates fibrosis (32, 33). Thus, the increased SHP expression seen in β-catenin KO after BDL is in line with previous reports describing an improvement in phenotype through reduction of BA synthesis and metabolism.…”
Section: Discussionsupporting
confidence: 61%
“…The critical antifibrotic role of Shp has been documented in the literature. An earlier study (47) demonstrated that disruption of Shp exacerbates bile duct ligation-induced cholestatic liver fibrosis, whereas Shp overexpression or increasing Shp expression by pharmacological compounds attenuates hepatic fibrosis induced either by hepatitis C virus infection (48) or by carbon tetrachloride and ␣-naphthyl-isothiocyanate (49). In addition, increasing Shp mRNA levels in HSCs by FXR ligands abrogates thrombin-and TGF-␤1-induced up-regulation of ␣1 collagen mRNA (50).…”
Section: Dissociation Of Steatosis From Inflammation By Shp Deletionmentioning
confidence: 99%
“…Interestingly, the SHP interacting proteins are mainly nuclear receptors (such as FXR, ER, LXR, PXR, RAR, CAR, and PPAR) or other transcription factors (such as BMAL1, c-Jun, SREBP-1c, FOXO1, p65, and USF1), and dimerization with SHP usually leads to transcriptional repression of their target gene (117). These interactions regulate complex networks of metabolism, hemostasis and immune responses (52,117,118).…”
Section: Small Heterodimer Partner (Shp)mentioning
confidence: 99%